1998
DOI: 10.1063/1.368475
|View full text |Cite
|
Sign up to set email alerts
|

Ballistic electron emission microscopy study of barrier height inhomogeneities introduced in Au/n-Si Schottky contacts by a HF pretreatment

Abstract: Articles you may be interested inSchottky barrier height measurements of Cu/Si(001), Ag/Si(001), and Au/Si(001) interfaces utilizing ballistic electron emission microscopy and ballistic hole emission microscopy Mechanisms for the reduction of the Schottky barrier heights of high-quality nonalloyed Pt contacts on surfacetreated p-GaNThe distribution of Schottky barrier heights over the contact area in Au/n-Si diodes was determined by ballistic electron emission microscopy. For samples on which an aqueous HF pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(31 citation statements)
references
References 20 publications
4
27
0
Order By: Relevance
“…There is experimental evidence [28][29][30] that nanometer-sized lateral variations in SBH exist at many metal semiconductor interfaces. Olbrich et al [28] have recently shown that potential pinch-off effect can be observed near intentionally introduced low-barrier height areas in Au/Co/GaAsP diodes, and that these low-barrier areas correlate well with the effective barrier height of the entire diode.…”
Section: Discussionmentioning
confidence: 99%
“…There is experimental evidence [28][29][30] that nanometer-sized lateral variations in SBH exist at many metal semiconductor interfaces. Olbrich et al [28] have recently shown that potential pinch-off effect can be observed near intentionally introduced low-barrier height areas in Au/Co/GaAsP diodes, and that these low-barrier areas correlate well with the effective barrier height of the entire diode.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the organic pyronine-B layer modifies the electrical properties of the n-InP Schottky diode. The studies in literature have shown that effective Schottky barrier could be either increased or decreased by using organic thin layer on inorganic Si semiconductor [61][62][63][64][65][66]. It is evaluated that the interface properties of the diode is passivated by using organic layer surface to reduce the interaction between metal and inorganic.…”
Section: The Current-voltage Characteristics As Function Of Temperaturementioning
confidence: 99%
“…Also, several authors have reported experimental evidence that nanometer-sized lateral variations in BHs exist [45][46][47]. This result has been attributed to the barrier inhomogeneities.…”
Section: Introductionmentioning
confidence: 86%